Pengaruh Kualitas Layanan, Persepsi Nilai dan Kepuasan Nasabah terhadap Loyalitas Nasabah Bank - Setiawan, Heri (Universitas Muhammadiyah Palembang, 2017)
Purpose - This study aims to examine the effect of service quality,perceived value and customer satisfaction on customer loyalty ofbank service in Palembang City.Design/methodology - Data collected by questionnaire with thenumber of respondents is 184 respondents and the approach ofsampling technique used is purposive sampling.Findings – The result of the research explain that service qualityhave positive and significant effect on customer loyalty. Perceivedvalue have a positive and significant effect on consumer loyalty.Consumer satisfaction have a positive and significant effect onconsumer loyalty. Then, service quality, perceived value andconsumer satisfaction have a positive and significant effect onconsumer loyalty. The results showed that the convenienceprovided by banking favored by consumers. Therefore, banksshould look for alternative strategies designed to improve services,and interaction between bank employees and consumers.